2020
DOI: 10.1103/physrevapplied.13.054008
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent Thermal Conductivity of a Single Germanium Nanowire Measured by Optothermal Raman Spectroscopy

Abstract: We investigate temperature dependent thermal conductivity 𝜅(𝑇) in a single Ge nanowire (NW) using Optothermal Raman Spectroscopy which utilizes the temperature dependence of Raman lines as a local probe for temperature. The experiment was done from 300 K to above 700 K, a temperature range in which thermal conductivity of single NWs has been explored rarely. The thermal conductivity of Ge NWs (grown by vapor liquid solid mechanism), at around room temperature were observed to lie in the range 1.8 -4.2 W/m.K … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Temperature dependent Raman spectroscopy is a simple, convenient and contact Paper Nanoscale less method for probing the thermal properties of 2D as well as 1D nanostructures. 42,43 The temperature dependent Raman modes of Ge 1−x Sn x (x = 0.01, 0.06 and 0.08) alloy NWs were investigated over a temperature range between 83 and 523 K. Fig. 5 shows the temperature dependent Raman modes of the NWs estimated from the temperature dependent Raman data presented in Fig.…”
Section: Temperature-dependent Raman Spectroscopymentioning
confidence: 99%
“…Temperature dependent Raman spectroscopy is a simple, convenient and contact Paper Nanoscale less method for probing the thermal properties of 2D as well as 1D nanostructures. 42,43 The temperature dependent Raman modes of Ge 1−x Sn x (x = 0.01, 0.06 and 0.08) alloy NWs were investigated over a temperature range between 83 and 523 K. Fig. 5 shows the temperature dependent Raman modes of the NWs estimated from the temperature dependent Raman data presented in Fig.…”
Section: Temperature-dependent Raman Spectroscopymentioning
confidence: 99%
“…The first studies of the thermal properties of single-layer graphene were conducted by Balandin et al [ 179 , 180 ] using Raman thermometry. Since then, Raman thermometry has been used in a wide range of 2D materials [ 22 , 73 , 98 , 181 , 182 , 183 , 184 , 185 ], carbon nanotubes [ 186 ], nanowires [ 187 , 188 , 189 ], nanomembranes [ 190 , 191 , 192 , 193 ], and phononic crystals [ 24 , 33 ], among others. In general, the 2D material is transferred over a substrate, which was previously patterned with micro-holes and covered with metal layer to ensure a good thermal contact.…”
Section: Experimental Techniques For Thermal Characterizationmentioning
confidence: 99%
“…Recently, we have used temperature-dependent Raman spectroscopy (opto-thermal spectroscopy) to measure the temperature-dependent κ of single Ge NWs down to an NW diameter of 50 nm in the temperature range of 300−700 K. 16 The results showed that in addition to the boundary scattering, the temperature dependence of κ (given as κ ∝ 1/T) is primarily controlled by the Umklapp process of phonon− phonon interaction which is determined by the anharmonicity and can be parameterized by γ. The discussion above highlights the importance of knowledge of the thermal parameters, which are difficult to measure directly through experiments.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we have also simulated the phonon mean free path and compared the simulation with the data obtained from recent experimental measurements of κ. 16 Two well-characterized ensembles of Ge NWs were used for the investigation. One was oxygen-free, pristine Ge NWs only with native surface oxide (thickness ≤2 nm), and the other was Ge NWs with a surface oxide thickness of ∼5−10 nm and thus can be considered as a core−shell type.…”
Section: Introductionmentioning
confidence: 99%